GENERATION Z PERCEPTIONS AND THE INVESTMENT FEASIBILITY OF BATIK MSMES: EVIDENCE FROM THE CAPITAL ASSET PRICING MODEL - Margaretha Prihatiningsih; Yusup Hari Subagya; Raymond Gunanta (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This study investigates the influence of Generation Z perceptions on the investment feasibility of Esti Dina Collection Batik MSMEs using the Capital Asset Pricing Model (CAPM). A quantitative explanatory approach was employed with data collected from Generation Z university students through a structured questionnaire. Data were analyzed using descriptive statistics and Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that student perceptions positively influence income improvement and the application of CAPM in evaluating MSME investments. Income improvement also mediates the relationship between investor perceptions and CAPM adoption. These findings suggest that investment decisions among Generation Z are driven not only by expected returns but also by economic expectations and business sustainability considerations. The study contributes to behavioral finance literature by integrating psychological and financial perspectives in evaluating investment opportunities within cultural-based MSMEs. Keywords: Generation Z, CAPM, MSMEs, Investment Feasibility, Behavioral Finance, Batik Industry.